2019
DOI: 10.1038/s41598-019-47365-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-EIF3A autoantibody as a potential diagnostic marker for hepatocellular carcinoma

Abstract: Tumor-associated autoantibodies are promising diagnostic biomarkers for early detection of tumors. We have screened a novel tumor-associated autoantibody in hepatocellular carcinoma (HCC) model mice. Its target antigen was identified as eukaryotic translation initiation factor 3 subunit A (EIF3A) by proteomic analysis, and the elevated expression of EIF3A in HCC tissues of tumor model mice as well as human patients was shown. Also, its existence in tumor-derived exosomes was revealed, which seem to be the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…We constructed a B-cell hybridoma pool using tumor-bearing transgenic mice, enriched with B cell hybridomas producing HCC-associated autoantibodies. Several TA autoantibodies from these B cell hybridoma cells have been characterized and proposed as biomarkers for cancer diagnosis [ 19 , 22 , 23 , 24 ]. In this study, another monoclonal TA autoantibody, named XC154 mAb, which bound specifically to human tumor cells, was purified, and its antigenic characteristics were characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a B-cell hybridoma pool using tumor-bearing transgenic mice, enriched with B cell hybridomas producing HCC-associated autoantibodies. Several TA autoantibodies from these B cell hybridoma cells have been characterized and proposed as biomarkers for cancer diagnosis [ 19 , 22 , 23 , 24 ]. In this study, another monoclonal TA autoantibody, named XC154 mAb, which bound specifically to human tumor cells, was purified, and its antigenic characteristics were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have identified an anti-ATIC autoantibody as a novel autoantibody biomarker for liver cancer. HBx-transgenic HCC-model mouse [ 19 , 20 ] was used to obtain B cell hybridomas producing TA autoantibodies, and a monoclonal TA autoantibody, XC154, was purified and characterized. Its specific TA antigen was identified as ATIC, a purine synthesis protein overexpressed in human tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…eIF3a is upregulated in HCC and facilitates the translation of HIF-1α, which, in turn, regulates glycolytic metabolism (22). Additionally, a serum anti-eIF3a autoantibody has been identified as a potential diagnostic biomarker for HCC, further supporting the role of eIF3a in HCC (37). However, the mechanism underlying the upregulation of eIF3a and the functions of eIF3a on the proliferation and metastasis in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…A routine task for proteomics laboratories and core facilities has long been the identification and characterization of the proteins from specific regions of a gel-based separation [27]. Despite the age of these gel-based methods, these types of analyses are still valuable for answering specific biological questions [2831]. In these settings, a common goal is to detect the proteins—and potentially the post-translational modifications—that are present within an excised band from a 1-dimensional SDS-PAGE gel.…”
Section: Resultsmentioning
confidence: 99%